Retraction Note to: Importance of Forestry and its Role in Reduction of Poverty in Swat Valley, KPK, Pakistan - Ahmad, Waqar; Yan, Tingwu; Hassan, Suhair; Bibi, Aqsa (Asian Development Policy Review, 2018)
Farm forestry plays a significant role in the reduction of poverty and natural resource protection. This study shows the importance of forest and its role in the reduction of poverty. The study was accompanied in January to march, 2018. Collection of data a well–designed questionnaire was used and sixty (60) respondents were selected from ten (10) villages through randomly in the study area. From the study, it is clear that daily wood need was 19.76 kg per household while annual requirements were 61.41 cubic feet per household and majority obtain from forest trees. The study also showed that forest plays a key role in income generation and the reduction of poverty of household.in the study area average income from farm trees were PKR 517558.13 per household. While on the other hand study shows that farm trees have a significant role in natural resource conservation which reduces pressure on natural forest, provide wildlife habitat and soil conservation. Chi-square test was used to know the positive role of farm forestry in poverty reduction and natural resource conservation.